2018
DOI: 10.1007/s10554-018-1396-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac myxoma: a contemporary multimodality imaging review

Abstract: Cardiac myxoma (CM) is by far the most common primary benign cardiac tumor, typically arising in the left atrium with an attachment point in the fossa ovalis region. Although the etiology of CM remains unclear, we know that this endocardial-based mass originates from undifferentiated mesenchymal cells. Continuous technical improvements in the field of echocardiography since the 1960s has profoundly changed the diagnostic approach by allowing a good tumor detection as well as the preoperative planning by provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 87 publications
0
64
0
4
Order By: Relevance
“… 6) 7) Cardiac myxomas have been well known as the most frequent primary benign cardiac tumors in adults accounting for 50–85% of them. 2) 7) TTE is a widely available, noninvasive diagnostic method for initial evaluation of cardiac myxomas. In recent years, various imaging studies including TTE are conducted for health screening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 6) 7) Cardiac myxomas have been well known as the most frequent primary benign cardiac tumors in adults accounting for 50–85% of them. 2) 7) TTE is a widely available, noninvasive diagnostic method for initial evaluation of cardiac myxomas. In recent years, various imaging studies including TTE are conducted for health screening.…”
Section: Discussionmentioning
confidence: 99%
“… 13) 14) 15) 16) LA is the well-known, most prevalent site of myxomas with the incidence of 77–95% in recent studies, 8) 9) 10) 17) 18) and 80% of which are attached to the interatrial septum ( Table 5 ). 2) Tumors other than myxomas found in the LA cavity might be confused with myxomas and myxomas involving the sites other than the LA may be mistaken for other tumors. Garatti et al 18) reported that among 102 patients with preoperative diagnosis of myxomas, 4 patients (3.9%) with LA tumors were confuted by pathology after surgery, 3 of which were found to be thrombus and one was primary cardiac sarcoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large, thin, and hypermobile forms are unusual . The frequency of recurrence is about 22% for complex forms and 12% for other familial forms and 1% to 3% for sporadic myxomas, which seldom recur after surgery . Although, 2D and RT‐3D TEE show usually accurate imaging capabilities to detect the myxoma, further imaging methods including computed tomography, cardiovascular magnetic resonance imaging, and 18 F‐fluorodeoxyglucose positron‐emission tomography/computed tomography may be useful for diagnosis .…”
Section: Case Reportmentioning
confidence: 99%
“…CMs are usually solitary and are attached to the interatrial septum (IAS) at the border of the fossa ovalis, usually protruding into the left atrium (LA) but occasionally into the right atrium (RA) and rarely into the ventricles. 3) 5) The mobility of the tumor depends upon the extent of attachment to the IAS and the length of the stalk. CMs vary in size from 1–15 cm (mean 3–4 cm) in diameter.…”
mentioning
confidence: 99%